An Improved Array Steering Vector Estimation Method and Its Application in Speech Enhancement - Meng Hwa Er; Zhu Liang Yu (EURASIP Journal on Advances in Signal Processing, 2005)
We propose a robust microphone array for speech enhancement and noise suppression. To overcome target signal cancellation problem of conventional beamformes caused by array imperfections or reverberation effects, the proposed method adopts arbitrary transfer function relating each microphone and target speech signal as array channel model. This is achieved in two ways. First, we propose a method to estimate the array steering vector (ASV) by means of exploiting the nonstationarity of speech signal to combat stationary noise and interference. Next, with the estimated ASV, a robust matched-filter-(MF-) array-based generalized sidelobe canceller (MF-GSC) is constructed to enhance the speech signal and suppress noise/interference. In addition, it also has the capability to reduce the reverberation effects of the acoustic enclosure. Numerical results show that the proposed method demonstrates high performance even in adverse environments.